Zebra finch as a developmental model. Issue 11 (1st October 2015) - Mak, Siu‐Shan; Wrabel, Anna; Nagai, Hiroki; Ladher, Raj K.; Sheng, Guojun
Summary: The domesticated zebra finch ( Taeniopygia guttata ) is a well‐established animal model for studying vocal learning. It is also a tractable model for developmental analyses. The finch genome has been sequenced and methods for its transgenesis have been reported. Hatching and sexual maturation in this species takes only two weeks and three months, respectively. Finch colonies can be established relatively easily and its eggs are laid at a stage earlier than in other common avian experimental models, facilitating the analysis of very early avian development. Representing the Neoaves to which 95% of all bird species belong, the finch can potentially complement two existing, Galloanserae developmental models, the chick, and quail. Here, we provide a step‐by‐step guide for how to set up a finch colony in a conventional laboratory environment. Technical tips are offered to optimize hens' productivity and ensure a constant supply of fertilized finch eggs. Methods of handling finch eggs and embryos for subsequent embryological, cellular, or molecular analyses are also discussed. We conclude by emphasizing scientific values and cost effectiveness of maintaining a finch colony for avian developmental studies. genesis 53:669–677, 2015. © 2015 Wiley Periodicals, Inc.